(untitled) (Global Journal of Science Frontier Research, 2014)
Birds are a serious problem at airports threat to aviation safety. Since the early days of aviation, collisions of aircraft and birds have taken place, sometimes with fatal consequences. Generally, the damage due to their size of the bird species involved, hunting behavior, and hovering/soaring habits. The combination of abundant food sources, open space, and availability of perching structures on airport grounds and near runway/taxiway areas provides ideal hunting opportunities for many raptors. Also, the behavior of bird species influences the risks, for instance flocking or certain migration patterns and flying altitudes. Development of larger, faster and quieter aircraft, jet engines and intensification of air traffic caused an increase in the number of incidents. Military exercises involve flying at high speed an low altitude, and are exposed to a more serious risk.